Impact of Brand Identity and Brand Identity-Cognitive Style Fit on Consumer-Based Brand Equity with Brand Image as a Mediating Variable in Toko Kecil Club - Gradiyanto, Adrian; Nurbasari, Anny; Agus, Herdiansyah (The Journal of Management, Digital Business, and Entrepreneurship, 2024)
Brand value that is based on consumers (consumer-based brand equity) and is developed through brand identity that is by consumers' thinking characteristics is still very limited, even though consumers' ways of thinking are very diverse. This research aims to determine the influence of brand identity and brand identity that matches consumers' way of thinking (BICS fit) on CBBE, which is linked to the mediating variable (brand image). Using the explanatory research method, 11,000 Instagram followers of the Toko Kecil club became the population. The sample consisted of 386 people (slovin) using a simple random sampling technique. The results of this research show that brand identity has a positive effect on CBBE, brand identity has a positive effect on brand image, brand image has a positive effect on CBBE, brand identity mediated by brand image has a positive effect on CBBE, BICS fit has a positive effect on CBBE, BICS fit has a positive effect on brand image, brand image has a positive effect on CBBE, BICS fit which is mediated by brand image has a positive effect on CBBE. The results of this research can help clubs strategically overcome problems that arise and can provide a deeper understanding of the importance of brand identity, cognitive style, and brand image in achieving CBBE in the futsal club industry.